(3eaQM GdfaSs - (3eLO GdOjf YHO GdhgGH Hf SMfhf GdJfhNj,J (B694 (3g` s ((3EHQGgje Hf YHO GdQMef GdfGSN GdWQGHdSi GdMfai s)
(3ChdgG (B:s
(3CeG HYO MeO Gddg NGdb GdOGA hGdOhGA , GdefbP ef GdCYQGV hGdOhGA , HeaQMGJ GdfLGI hGdTaGA aEffi deG CWdYJ Ydi CcKQ GdcJH GdWHjI ade CLO ajgG eG jTai GdbdH ai PcQ GdCehQ GdeaQMI ddfaS s
(3BNQgG (B:s
(3GdTQHI hRf eKbGd HTQGH JaGM TGei hMeGV HeGA dSGf KhQ heGA hQO , fGaY Ef TGA Gddg Je GdcJGH s
(3fSNI NRGFfjIs
(3hGfXQ agQS GdWH HQbe (B236 " (3eaQL GdfaS (B"s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B240 s
Keywords: (3GdWHs